Level of maternal self-efficacy in Adolescents from the northeast region of Guanajuato, México - Ramírez Robles, Marisol (2022)
Objective: Describe and analyze the level of Maternal Self-efficacy in adolescents from a second level hospital in the state of Guanajuato, in Mexico. Method: It was applied to adolescent mothers who attended a Maternity Hospital in the state of Guanajuato, the Perceived Maternal Parental Self-efficacy scale (α=0.98) was used, which consists of 20 Likert-type items and four subscales, as well as an identification card semi-structured for sociodemographic data, the latter, validated by experts. Ethical considerations were taken into account. Main Results: 72.7% of adolescent mothers presented a low level of self-efficacy, characterized by lack of ability and little experience in maternal care. Overall Conclusion: Maternal self-efficacy in adolescents is low, given the characteristics of development at this stage, coupled with motherhood, some mothers face the birth of a premature child, who in most cases ends up being hospitalized, having repercussions once More on self-efficacy. For nursing, adolescent mothers present a challenge for care, therefore, the need to describe this phenomenon is identified in order to create educational interventions based on maternal self-efficacy in adolescents.